Thermal performance enhancement in electric motor rotors: Evaluating the impact of rotating heat pipes - Rezqi, Khairu; Putra, Nandy; Sholahudin, Sholahudin; Kiswanto, Gandjar (BKS-TM Indonesia, 2025)
Effective thermal management is essential in high-performance electric motors, where rotor overheating accelerates demagnetization and reduces operational lifespan. This study investigates a horizontally mounted, wick based rotating heat pipe (RHP) as a passive cooling solution for an induction motor rotor. The system was subjected to stepped heat loads 20, 25, 30, and 35 W, also and speeds 0, 250, 500, 750 RPM, with time resolved measurements acquired to evaluate steady state thermal resistance (Rth) and transient response. The results reveal a non monotonic relationship between rotational speed and thermal performance. Contrary to initial assumptions, the RHP achieved its lowest Rth of 0.164 °C/W not at standstill, but at a moderate speed of 250 RPM. This performance peak is attributed to a balanced interplay where gentle centrifugal force enhances capillary-driven liquid distribution, maximizing effective evaporation without inducing flow instability. Compared to the solid rotor baseline, the RHP consistently reduced rotor temperatures by up to 6 °C and lowered thermal resistance by more than 70%. Additionally, the RHP halved the thermal time constant following each power step, indicating superior transient regulation. The identification of an optimal rotational speed window, distinct from any transitional instability zone, offers critical design insight for embedding RHPs in next-generation electric machines where spatial constraints and thermal reliability are paramount.